Effectiveness of Collaboration Skills Assessment Instrument in Physics Practicum: A Case Study with the Rasch Model - Saiyidah Mahtari; Syihabuddin Syihabuddin; Agus Setiawan; Mustika Wati (Dinasti Publisher, 2025)
Collaboration skills in the 21st century are becoming an important aspect in education and the professional world. This study aims to analyse the validity and reliability of collaboration skills instruments using the Rasch Model. Quantitative method with survey design was applied to 100 students of Physics Education Study Programme at Universitas Lambung Mangkurat. Data was collected through a questionnaire consisting of 20 items, and analysis was conducted to measure item difficulty as well as individual ability using Rasch Model. The analysis results showed that after data cleaning, the assessment instrument had good reliability, with Person Reliability reaching 0.80 and Item Reliability 0.90. Results also identified that the most difficult collaboration skills to achieve were individual accountability and personal responsibility, whereas positive interdependence was relatively easier to achieve. This research provides important insights for collaboration skills assessment instruments in the context of physics education practicum, as well as recommendations for improving collaboration skills.